Ionically bound peroxidase from peach fruit - Neves, Valdir Augusto [UNESP] (Inst Tecnologia Parana, 2002)
Soluble, ionically bound peroxidase (POD) and polyphenoloxidase (PPO) were extracted from the pulp of peach fruit during ripening at 20degreesC Ionically bound form was purified 6.1 -fold by DEAE-cellulose and Sephadex G-100 chromatography. The purified enzyme showed only one peak of activity on Sephadex G-100 and PAGE revealed that the enzyme was purified by the procedures adopted. The purified enzyme showed a molecular weight of 29000 Da, maximum activity at pH 5.0 and at 40degreesC the calculated apparent activation energy (Ea) for the reaction was 10.04 kcal/mol. The enzyme was heat-labile in the temperature range of 60 to 75degreesC with a fast inactivation at 75degreesC Measurement of residual activity showed a stabilizing effect of sucrose at various temperature/sugar concentrations (0, 10, 20 %, w/w), with an activation energy (Ea) for inactivation increasing with sucrose concentration from 0 to 20% (w/w). The Km and V-max values were 9.35 and 15.38 mM for O-dianisidine and H2O2, respectively. The bound enzyme was inhibited competitively by (.)ferulic, caffeic and protocatechuic acids with different values of Ki,. L-cysteine, p-coumaric and indolacetic acid and Fe++ also inhibited the enzyme but at a lower grade. N-ethylmaleimide and p-CMB were not effective to inhibit the enzyme demonstrating the non-essentiality of SH groups.
Keywords: peach peroxidases; ripening; purification; kinetics; heat stability